THE EFFECT OF WORKING DISCIPLINE ON PERFORMANCE OF EMPLOYEES IN PT KERETA API INDONESIA (PERSERO) DAOP 1 JAKARTA - Helmut Martahi Saoloan Tambunan; Khotimah Herliana; Faif Yusuf (Kusuma Negara Business School, 2012)
In this study there are two variables namely X (Work Discipline) and Y (Employee Performance) variable. This research was conducted to determine the Performance of Employees and the effect of Work Discipline on Employee Performance at PT.Kereta Api Indonesia (Persero) DAOP 1 Jakarta. The method used in this study is a quantitative method of analysis to discuss the identification of the problem of how the Employee Performance of PT.Kereta Api Indonesia (Persero) DAOP 1 Jakarta and analysis to discuss the problem identification of how much influence the Work Discipline has on the Employee Performance of PT.Kereta Api Indonesia (Persero ) DAOP 1 Jakarta. The data used are primary data collected through observation, questionnaire methods, interviews, and library methods. To measure the effect of these variables used the validity test, the reliability equation regression test, the coefficient of determination, the validity test and the reliability test with the help of a computer application program SPSS 23.0 Based on the results of data analysis using statistical methods namely the results of the validity test, the reliability test with valid and reliable results , Correlation Coefficient Test Results of 0.843 which means a strong and direct relationship between the independent variable (Work Discipline) with the dependent variable (Employee Performance). From the results of the Regression Analyst, the equation can be obtained, namely: Y = 5,960 + 0,842 X. So Y = Employee Performance, and X = Work Discipline. From the results of the calculation of the regression equation about the effect of Work Discipline on Employee Performance of PT.Kereta Api Indonesia (Persero) DAOP 1 Jakarta is having a positive or direct relationship between Work Discipline influencing Employee Performance.